A More-than-Human Ecology: Evolving Generative Artificial Intelligence in Higher Education - James Fern (MDPI AG, 2024)
The significant improvements in generative artificial intelligence (GenAI) observed in recent years present higher education with both an opportunity and a significant challenge. Its successful integration will require careful planning and sound pedagogical underpinnings, both in regard to learning and teaching as well as assessment and feedback. Drawing upon theories from the more-than-human world, as well as concepts such as originality, equality, and sustainability, it is possible to develop a dialogue around GenAI that places the students' learning journey at the heart of the discussion.